Automatic jump detection method for athlete monitoring and performance in volleyball - Gageler, W. H.; Wearing, S.; James, D. A. (International Journal of Performance Analysis in Sport, 2015)
Athlete performance and monitoring is an area of interest across many sporting codes, for indoor sports however, the primary methods of athlete monitoring are manually recording statistics or video analysis.